2007
DOI: 10.4067/s0717-77122007000200003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de triatominos infectados con Trypanosoma cruzi en el litoral de la ciudad de Arica

Abstract: It has been observed throughout

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
5
2
Order By: Relevance
“…The infection on the captured specimens reached 5.8% (3/52 specimens analysed). These values are lower than those reported by Carvajal et al (2007) and Botto-Mahan et al (2008) for this species and those found by Toledo et al (2013) in the same sampled sections; although the differences in infection found by Toledo et al (2013) could be explained by the fact that most of our specimens collected in San Marcos were associated with birds, in which the parasite does not reproduce owing to the mechanism of natural resistance to the parasite (Kierszenbaum et al, 1976).…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…The infection on the captured specimens reached 5.8% (3/52 specimens analysed). These values are lower than those reported by Carvajal et al (2007) and Botto-Mahan et al (2008) for this species and those found by Toledo et al (2013) in the same sampled sections; although the differences in infection found by Toledo et al (2013) could be explained by the fact that most of our specimens collected in San Marcos were associated with birds, in which the parasite does not reproduce owing to the mechanism of natural resistance to the parasite (Kierszenbaum et al, 1976).…”
Section: Discussioncontrasting
confidence: 59%
“…These values are lower than those reported by Carvajal et al . () and Botto‐Mahan et al . () for this species and those found by Toledo et al .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Morphological and cytogenetic data indicated that the populations that border the distributions of M. gajardoi and M. spinolai, belong to a different species of parapatric origin. (Sagua et al 2000, Canals et al 2001, Carvajal et al 2007, Botto-Mahan et al 2008. This disease is important in the Neotropical region with nearly 16 million people infected, and another 90 million at risk of contracting the disease, especially in rural areas (Schofi eld et al 1982, Schofi eld 1994.…”
mentioning
confidence: 99%
“…Three species of Reduviidae insect are transmitters of Chagas' disease to mammals, including humans, in Chile: Triatoma infestans, Triatoma spinolai, and Mepraia gajardoi (3,13). Modes of transmission of Chagas' disease other than infections through insect vectors have been documented to occur in Chile, including accidental laboratory infections, infections caused by blood transfusion, and transplacental infections.…”
mentioning
confidence: 99%